PENGGUNAAN GELAR KHALIFAH PADA TAREKAT NAQSABANDIYAH DI KABUPATEN LABUHANBATU SELATAN - Janna, Dely Aulia; Ismail, Ismail (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2024)
This research aims to analyze the use of the title caliph in the context of the Naqsabandiyah Babussalam Tarekat in South Labuhanbatu Regency. This research shows that being a Khalifah of Allah is a gift that is given a mandate to obey Allah’s commands, to look after the heavens and the earth, especially the environment where you live. The Caliph can preserve the environment if he can implement several characters that must be present in a leader. For example, the character of commitment, sincerity, fairness, honesty, istiqomah and so on. This research uses a qualitative descriptive research method which aims to understand the phenomena experienced by research subjects such as behavior, perception, motivation, actions and so on holistically and by means of descriptions in the form of words and language as well as through in-depth interviews with participants. Caliph, murshid, and member of the tarekat, this research reveals that the title Caliph not only has spiritual meaning, but also functions as a symbol of leadership and authority in the community. Further analysis shows that the use of this title is influenced by local historical, social and cultural factors, as well as the dynamics of the relationship between the congregation and the wider community. It is hoped that the research results can contribute to a more comprehensive understanding of the socio-religious dynamics in South Labuhanbatu Regency, especially in the context of the development of the congregation and the use of religious titles.